(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This work is focused on the analysis of the prehistoric lithic industry found in secondary context in the Etruscan settlement of Forcello di Bagnolo S. Vito (MN). During thirty years of excavations, the University of Milan had found three axes and 123 flint artifacts, such as blades, flakes, cores and instruments. Here I analyze every artefact from a typological point of view and try to put them in the right chronological bounds, finding comparisons with similar objects from certain stratigraphical contexts from Bagnolo S. Vito’s territory and neighborhoods. I also try to find out how they arrived there, in a VI-IV century B.C. settlement, through the examination and interpretation of every stratigraphical unit in which they were found.